The student writer : - Clouse, Barbara Fine. (McGraw-Hill Higher Education, 2010)
Pt.1. Strategies for Reading and Writing ; Pt.2. Patterns of Development ; Pt.3. Using the Patterns of Development ; Pt.4. A Brief Guide to Sentence Errors.